2021
DOI: 10.7494/geom.2021.15.3.39
|View full text |Cite
|
Sign up to set email alerts
|

Towards Transit‑Oriented Development for Sustainable Urban Mobility: Insights from a Central European City

Abstract: Sustainable Development Goals require holistic actions, including activity at the intersection of urban planning and environmental engineering. Turning our cities towards transit‑oriented development might help in reducing pollutant emissions caused by individual transportation modes that rely on crude oil. This research presents how the use of geospatial network analysis can support local decision makers in the evaluation of potential public transport accessibility by citizens in the case of a Central Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It can therefore be concluded that the lockdown, which was very noticeable to citizens during the first wave of COVID-19, caused a slight fluctuation in air quality, which had no consequences both throughout 2020 and over next years. This conclusion is important for local authorities, who have the task of introducing actions to improve the quality of inhabitants' lives [49,50] by, inter alia, improving the quality of the air inhabitants breathe. The conducted analysis shows that the actions aimed at limiting vehicle traffic must be long-term in order to be able to expect a lasting improvement in air quality.…”
Section: Discussionmentioning
confidence: 96%
“…It can therefore be concluded that the lockdown, which was very noticeable to citizens during the first wave of COVID-19, caused a slight fluctuation in air quality, which had no consequences both throughout 2020 and over next years. This conclusion is important for local authorities, who have the task of introducing actions to improve the quality of inhabitants' lives [49,50] by, inter alia, improving the quality of the air inhabitants breathe. The conducted analysis shows that the actions aimed at limiting vehicle traffic must be long-term in order to be able to expect a lasting improvement in air quality.…”
Section: Discussionmentioning
confidence: 96%
“…Recent literature has emphasized the role of technology and computer software tools in addressing these urban challenges. For instance, Leśniewski et al [19] highlight the importance of computer software tools (CS tools V2) in managing industrial symbiotic networks (ISNs), which involve multidimensional networks that operate as dynamic complex networks crossing natural, technical, social, and computer systems boundaries. They underline the benefits of using CS tools to enhance value and reduce financial and environmental costs by sharing services, utilities, or by-products/waste among stakeholders in ISNs.…”
Section: Introductionmentioning
confidence: 99%
“…Service network integration includes schedule integration, route and route integration, infrastructure network integration in the form of physical integration, namely the integrated infrastructure for several modes located in one building node. The integration of service networks and transportation infrastructure in the implementation of effective and efficient intermodal / multimodal transportation is realized in the form of interconnection at the transportation node which functions as a meeting point that facilitates switching modes (intermodal terminals) [1], [2], [5], [8], [23] and [24].…”
Section: Introductionmentioning
confidence: 99%